2013
DOI: 10.2147/dddt.s47272
|View full text |Cite
|
Sign up to set email alerts
|

Bioequivalence study of two formulations of candesartan cilexetil tablet in healthy subjects under fasting conditions

Abstract: IntroductionThe present study was conducted to compare the bioavailability of two candesartan cilexetil 16 mg tablet formulations (test and reference formulations).Materials and methodsThis study was a randomized, single- blind, two-period, cross-over study which included 24 healthy adult male and female subjects under fasting conditions. The pharmacokinetic parameters were determined based on the concentrations of candesartan (CAS 139481-59-7), using ultra-pressure high-performance liquid chromatography with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 5 publications
3
11
1
Order By: Relevance
“…Similar results were also obtained by Cooper-Dehoff and Elliott who compared patent and generic drugs of some blood pressure lowering agents that included beta-blockers, diuretics, and calcium antagonists [10]. Some other studies on clopidogrel and candesartan tablets also reported bioequivalence between their patent and generic products [11,12].…”
Section: Introductionsupporting
confidence: 75%
“…Similar results were also obtained by Cooper-Dehoff and Elliott who compared patent and generic drugs of some blood pressure lowering agents that included beta-blockers, diuretics, and calcium antagonists [10]. Some other studies on clopidogrel and candesartan tablets also reported bioequivalence between their patent and generic products [11,12].…”
Section: Introductionsupporting
confidence: 75%
“…The intrasubject CV of C max, AUC 0–t , and AUC 0–∞ for the pilot study (13.5%–15.0%) was lower than those in the pivotal study (22.8%–24.4%); however, they were within the range for similar (14.7%–33%) reported for healthy volunteer studies for candesartan . In conclusion, the 16‐mg candesartan cilexetil test formulation 2 was found to be bioequivalent to the innovator following a single‐dose crossover study in healthy fasted subjects.…”
Section: Discussionmentioning
confidence: 45%
“…in the pivotal study (22.8%-24.4%); however, they were within the range for similar (14.7%-33%) reported for healthy volunteer studies for candesartan. [10][11][12][13] In conclusion, the 16-mg candesartan cilexetil test formulation 2 was found to be bioequivalent to the innovator following a single-dose crossover study in healthy fasted subjects. The study met the ANMAT regulatory criteria for bioequivalence in healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…With this concept, drug regulators require that generic formulations should have equivalent clinical effects with its innovator counterparts, resulting in interchangeability of both products. In compliance with the requirement, we have also conducted bioequivalence studies on several generic formulations [21,22,23,24]. Our current study on pramipexole was carried out with the same requirements in mind.…”
Section: Discussionmentioning
confidence: 99%